Combinatorial optimization : 6th International Symposium, ISCO 2020, Montreal, QC, Canada, May 4-6, 2020, Revised selected papers /: 6th International Symposium, ISCO 2020, Montreal, QC, Canada, May 4-6, 2020, Revised selected papers. (2020) - Unknown
No abstract available